Body size, body composition, and cardiovascular disease risk factors in NFL players - Allen, T. W.; Vogel, R. A.; Lincoln, A. E.; Dunn, R. E.; Tucker, A. M. (The Physician and Sportsmedicine, 2010)
We characterized the size of active National Football League (NFL) players by multiple criteria and analyzed their relation to traditional cardiovascular disease (CVD) risk factors with the objective of further clarifying the occurrence of cardiovascular risk factors in different player positions. Methods: This cross-sectional study was conducted in professional athletic training facilities. The participants were 504 active veteran players from a convenience sample of 12 NFL teams, grouped as interior linemen (IL) or all others (AO). Comparisons were made between the NFL groups and an age-equivalent general population database. Results: The IL group was significantly larger than AO by all size measures. Both groups were significantly larger than the Coronary Artery Risk Development in Young Adults (CARDIA) group. Mean percent body fat measurements in AO (mean, 13.4%; 95% confidence interval [CI], 12.9%-14%) and IL (mean, 25.2%; 95% CI, 24.4%-26%) groups were lower than estimates for the general population. Systolic blood pressure (BP) was higher in IL (mean, 131 mm Hg; 95% CI, 129-133 mm Hg) than AO (mean, 126 mm Hg; 95% CI, 125-127 mm Hg) and greater in both groups compared with the CARDIA group (mean, 112 mm Hg; 95% CI, 111-112 mm Hg). Mean low-density lipoprotein cholesterol and high-density lipoprotein cholesterol (HDL-C), total cholesterol, triglycerides, and glucose were within the normal range for both IL and AO. Interior linemen had significantly lower HDL-C than AO and the CARDIA group. Both NFL groups had significantly lower fasting glucose than CARDIA. Conclusion Body fat in active NFL players was lower than predicted by standard measures of obesity. Although the players were large, they were in the normal range for most CVD risk factors. Mean BP in the prehypertensive range was found in both NFL position groups, but was significantly higher in IL than in AO. Prehypertension in these athletes warrants vigilance.